Impact of Postural Corrective Training (TCP®) on overall glycemic control in diabetic middle-aged women (Research, Society and Development, 2022)
Introduction: Diabetes mellitus (DM) is a disease manifested by chronic hyperglycemia resulting from changes in the secretion and / or action of insulin, which can cause tissue damage. The practice of physical exercise is often recommended in the treatment of this disease because it improves glucose uptake due to increased insulin sensitivity. Objective: to evaluate the effect of Corrective Postural Training (TCP®) on the glycemic metabolism of patients with type 2 diabetes. Methods: Twenty-one women between 44 and 55 years old were divided into four groups: sedentary diabetics (SD); exercised diabetics (ED); non-diabetic exercised (NE); and non-diabetic sedentary (NS). TCP® was performed 3 times / week, for 1 hour / day, for a period of 20 weeks. Blood samples were collected pre- and post-intervention to determine cholesterol, triglycerides, HDL, fasting glycemia, glycated hemoglobin, estimated mean glycemia and cortisol. The Wilcoxon and Friedman tests were used to compare the results before and after intervention. Results: there was no significant difference in the anthropometric, biochemical and hormonal variables of all groups; however, glycated hemoglobin showed a significant difference (p